Quantifying Response to Nutrition Therapy During Critical Illness: Implications for Clinical Practice and Research? A Narrative Review. Issue 2 (20th July 2020) - Fetterplace, Kate; Ridley, Emma J.; Beach, Lisa; Abdelhamid, Yasmine Ali; Presneill, Jeffrey J.; MacIsaac, Christopher M.; Deane, Adam M.
Abstract: Critical illness causes substantial muscle loss that adversely impacts recovery and health‐related quality of life. Treatments are therefore needed that reduce mortality and/or improve the quality of survivorship. The purpose of this Review is to describe both patient‐centered and surrogate outcomes that quantify responses to nutrition therapy in critically ill patients. The use of these outcomes in randomized clinical trials will be described and the strengths and limitations of these outcomes detailed. Outcomes used to quantify the response of nutrition therapy must have a plausible mechanistic relationship to nutrition therapy and either be an accepted measure for the quality of survivorship or highly likely to lead to improvements in survivorship. This Review identified that previous trials have utilized diverse outcomes. The variety of outcomes observed is probably due to a lack of consensus as to the most appropriate surrogate outcomes to quantify response to nutrition therapy during research or clinical practice. Recent studies have used, with some success, measures of muscle mass to evaluate and monitor nutrition interventions administered to critically ill patients.